2013
DOI: 10.1371/journal.pone.0071354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Alzheimer’s Disease Progression Using Rate of Regional Hippocampal Atrophy

Abstract: Alzheimer’s disease (AD) is characterized by neurofibrillary tangle and neuropil thread deposition, which ultimately results in neuronal loss. A large number of magnetic resonance imaging studies have reported a smaller hippocampus in AD patients as compared to healthy elderlies. Even though this difference is often interpreted as atrophy, it is only an indirect measurement. A more direct way of measuring the atrophy is to use repeated MRIs within the same individual. Even though several groups have used this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 50 publications
(65 reference statements)
11
68
0
1
Order By: Relevance
“…This is in the same range as early disease-related brain volume alterations, for example in Alzheimer's Disease 11 . Automated brain segmentation software packages should therefore require strict MR parameter selection or include compensatory algorithms 12 to avoid MR-parameter-related bias of brain morphometry results.…”
Section: Discussionmentioning
confidence: 69%
“…This is in the same range as early disease-related brain volume alterations, for example in Alzheimer's Disease 11 . Automated brain segmentation software packages should therefore require strict MR parameter selection or include compensatory algorithms 12 to avoid MR-parameter-related bias of brain morphometry results.…”
Section: Discussionmentioning
confidence: 69%
“…Jack and colleagues have also reported that the odds ratio for progression to sporadic AD over 1.2-4.8 years is 1.75 in aMCI patients with smaller hippocampal volumes when compared to those with larger hippocampal volumes [32] . In a 3-year donepezil/vitamin E/placebo study of aMCI, Jack and colleagues further demonstrated a higher hippocampal atrophy rate (5.44%) in the placebo group than in the others [23] . Using hippocampal atrophy data from different time points (0, 6, 12, 18, 24, and 36 months), Leung and colleagues demonstrated that the rates in aMCI patients accelerated by 0.22%/ year 2 , and the acceleration of hippocampal loss may contribute to the progression of aMCI to AD [33] .…”
mentioning
confidence: 97%
“…Most of the studies found that smaller hippocampal volumes, predominantly in the subicular and CA1 areas, are related to an increased risk for conversion from aMCI to AD [20][21][22][23][24] , despite some inconsistent findings [25,26] .…”
mentioning
confidence: 99%
“…6). Although the difference in hippocampal volume had the same trend in many previous studies (Leung et al, 2010;Nestor et al, 2013;Frankó and Joly, 2013), the reported volumes substantially differed. The remarkable difference among studies could be due to the manual segmentation protocols used to define the atlases.…”
Section: Discussionmentioning
confidence: 57%
“…These techniques require the correspondence between the hippocampal segmentation of each subject to a template, and then a local analysis is performed (Styner et al, 2006;Gerardin et al, 2009;Frankó and Joly, 2013). In contrast, the surface roughness does not require any non-rigid registration.…”
Section: Discussionmentioning
confidence: 99%